PECULIARITIES OF CHANGE IN SEISMIC PROPERTIES OF FOREST SOILS WHEN FIXING THEM BY SILICATION METHODS. - Vakhitkhan ISMAILOV, Yodgorov Sharofiddin Ismatullaevich, Jonibek BOZOROV, Avazov Shuxrat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper presents the results of research on the use of silicatization methods to improve the physical and mechanical properties of loess soils during construction in seismically hazardous areas. It was found that silicatization of loess soils increases their seismic resistance, and under the studied regional conditions, the effect of silicatization is significantly higher. Certain advantages of the investigated methods and the possibility of their widespread use in the preparation of foundations for construction or their strengthening in the built-up area in seismically hazardous areas are revealed.